(untitled) (World Bulletin of Physical Education and Sports Science, 2025)
The article examines the effectiveness of modern training methods in optimizing volleyball players’ physical performance. The study was conducted over an 8-week experimental cycle involving 20 athletes who participated in a training program combining plyometric, interval, and functional exercises. The findings revealed significant improvements across multiple performance indicators: jump height increased by 18.6%, endurance by 12.3%, and passing accuracy by 10.3%, while reaction time and heart rate decreased by 13.1% and 4.3%, respectively. These results confirm that systematic application of scientifically grounded training principles—supported by digital monitoring and adaptive workload management—enhances explosive power, coordination, and endurance in volleyball players. The proposed methodology can be effectively implemented in professional sports academies and educational institutions to strengthen athletic performance and training efficiency.